(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Influence of Lignosilicon – plant growth and development activator, synthesized by IWC on the basis of wood chemical processing waste, and "Azotobakterin" bacterial products commercially produced by Bioefekts Ltd, on oats quality and harwest were tested in field conditions. Products were added to oat seeds into the box of seeding – machine before sowing. Three variants (each field of 1 ha) with different dosages of products applied were used: 10 and 40 kg/ha of lignosilicon and 400 g/ha of azotobacterin. It was shown that on the background of all products tested the harvest of oat increased significantly, vegetation time shortened, plant resistance to diseases increased, grain quality improved; most of all this indices changed positively on the background of lignosilicon (dosage of 40 kg/ha). The results obtained have demonstrated that lignosilicon and azotobacterin has good prospects for biological agriculture.